An analytical study of the cutoff conditions and dispersion curves of an optical fiber with a core slightly flattened on one side - Joshi M.; Singh V.; Prasad B.; Ojha S.P. (My University, 2025)
In this paper, we present a simple analytical method based on coordinate transformation for the calculation of the dispersion characteristics of an optical fiber which is slightly flattened on one side. We choose the new and appropriate orthogonal coordinates (ξ, η, z) for the proposed waveguide structure, and impose the boundary condition under a weak guidance condition to obtain the modal eigenvalue equation. Using this equation, we achieve numerical results in the form of dispersion curves and cutoff frequencies. © 2001 John Wiley & Sons, Inc.